Genome Diversity and Molecular Detection of PRRS Field Strains and Vaccine Strains, and PCV3 and PCV2 Strains - Y. Wang; F. Yuan; X. Liu; W. Zheng; H. Zhang; J. Zhang; K. Yoon; L. Peddireddi; Y. Fang; G. Anderson; J. Bai (Kansas Agricultural Experiment Station Research Reports, 2017)
Molecular diagnosis of porcine reproductive and respiratory syndrome virus (PRRS) and porcine circo virus (PCV) are challenging due to high genetic diversity in the viral genomes. Differentiating PRRS vaccine strains is even more challenging and is currently done by DNA sequencing, which is expensive and time-consuming. A multiplexed system (Luminex) allowing multiple detection targets in the same reaction is available. However, this system is not fully developed for common swine pathogens. Therefore, an assay was built to detect the majority of field PRRS strains by using different pairs of primers, and at the same time, to provide differentiation of the four PRRS vaccine strains used in the US by using vaccine-specific primers. Two sets of detection primer pairs were used that detect 85.4% and 91.2% of the 694 full genomes of the current PRRS collection in the GenBank. The combination of the 2 primer pairs will detect 98.1% of the genomes in the GenBank. Testing a limited number of field strains and the four vaccine strains (PrimePac, Ingelvac MLV, Ingelvac ATP, and Fostera) available in the US indicated that the assay detected all strains and identified each of the four vaccine strains correctly. Recently, clinical signs of porcine dermatitis and nephropathy syndrome, reproductive failure and multisystemic inflammation have been associated with PCV3. A real-time PCR assay is developed based on 67 PCV3 full-genome sequences with 100% detection rate. Also, 1,907 available PCV2 genomes were analyzed. Based on this analysis, 2 primer pairs were designed to detect an estimated 94.8% and 90.5% field strains, respectively, with a combined detection rate of 99%. The PCV3 and PCV2 assays were then combined into one reaction with an internal control to monitor the DNA extraction efficiencies. The combined multiplex assay detected all PCV3 and 99% of PCV2 strains with no cross-detection observed.
Keywords: PRRS; vaccine; PCV2; PCV3; molecular diagnostics; PCR; Luminex